Modeling The Quality of Teacher Services Based on "Growth Mindset" Facing Changes in Teaching and Learning Activities in The New Normal Era - Henny Suharyati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to build a model of teacher service quality based on a growth mindset to improve teaching and learning activities in the new normal era. Using a quantitative research design by disseminating teacher service quality and growth mindset instruments. The collected data were processed using descriptive and inferential data analysis techniques. The results of this study show that simple regression shows the influence of the growth mindset in modeling teacher service quality. This research indicator shows the strengthening of teacher service quality because it is supported by a growth mindset indicator with 5 criteria, as follows: 1) Assurance, namely a safe and secure condition that arises due to motivational support and challenges. 2) Reliability, namely achievement supported by motivation, perseverance, and courage to face difficulties. 3) Responsiveness, namely the ability to help is strengthened because of good motivation and mindset. 4) Tangibility, namely the need for physical evidence supported by the difficulties that will be faced because of the ability to respond to the situation at hand. 5) Empathy, namely attention, and concern, a positive mindset, trust, and openness will emerge.